Healing patterns of transplanted roots coated with an allogeneic fibrin-fibronectin concentrate: a histological study on the Chacma baboon Papio ursinus - Singh-Rambiritch, Simitha (My University, 2012)
This experiment was designed to evaluate whether an allogeneic fibrin-fibronectin protein concentrate (AFFP) can not only prevent ankylosis and root resorption of autotransplanted roots during healing but contribute to regenerate a periodontal attachment as well. In two adult male baboons (Papio ursinus), four horizontal alveoli, 2 to 3 mm deep, were prepared bilaterally in the buccal alveolar and basal bone adjacent to the first and second mandibular molars to receive the roots of the adjacent two molars. Following hemisection, the first and second mandibular molars were extracted, the coronal two-thirds of the roots were planed to remove the remnants of the periodontal ligament and cementum and a notch was placed at the junction between the planed and non-planed surfaces. The planed surfaces were demineralised with citric acid at pH 1 for 3 min. Before transplantation, the crowns were resected and the experimental roots and alveoli were coated with the AFFP prepared from pooled fresh-frozen baboon plasma. The animals were killed 55 days after the transplantations. Histometrical evaluation was performed on serial sections cut in a bucco-lingual direction parallel to the long axis of the transplanted roots. An analysis of variance, in relation to the extent of ankylosis and root resorption, revealed minimal differences between the treatments of experimental and control roots both in the planed and non-planed sections. In this primate autotransplantation model, the treatment with AFFP did not prevent ankylosis and root resorption and did not result in the establishment of a new periodontal attachment.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science Johannesburg, 2012
Keywords: primates; autotransplanted roots; fibrin-fibronectin concentrate